Factors to Consider in Syrian Refugee Families' Journeys to Social Inclusion: A Literature Review - Dodd, Jennifer; Clandinin, D. Jean; Vigneau, Gillian; Kubota, Hiroko; Caine, Vera (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2021)
This paper offers a review of the research literature on the experiences of young children and their families who left Syria as refugees and resettled in Canada. We identify five key factors that influence Syrian refugees’ experience of social inclusion within the context of the public-school systems as well as unveil the silences in and across the current studies. The five factors are pre-arrival experiences, mental health, social supports, acquisition of English language skills, and lack of preparedness of teachers and schools. Based on limited availability of research, we outline needed research to better understand social inclusion of Syrian refugee families with young children in Canada. There is a call to pay particular attention to their educational and social encounters.